Determination of geometrically necessary dislocations in large shear strain localization in aluminum. (1st October 2016) - Zhu, Chaoyi; Harrington, Tyler; Livescu, Veronica; Gray, George T.; Vecchio, Kenneth S.
Abstract: In this paper, a systematic approach is presented to quantifying shear band evolution by quantifying geometrically necessary dislocations (GND) associated with morphological anisotropy in 7039-aluminum alloy using the compact forced-simple shear (CFSS) design. A statistically motivated approach, i.e. the line averaged GND density profile, has been developed to investigate the GND density near heavily deformed, shear band regions. Our study shows that: i) line average GND density profiles for the Al samples machined in the A-direction (transverse to pancake-shaped grains), B-direction (parallel to longitudinal pancake-shaped grains, shearing in through-thickness direction), C-direction (parallel to pancake-shaped grains, shearing in the in-plane direction) and D-direction (parallel and through the pancake-shaped grains) are nominally similar; ii) apart from 7039-aluminum alloy C-direction that has a uniform GND distribution in the direction normal to shear due to a grain-sliding mechanism, GND profiles for other samples decrease steadily away from the shear band as plastic strain diminishes, in agreement with Ashby's theory of work hardening, iii) anisotropy in damage evolution and shear-stress shear-strain response of 7039-aluminum alloy is associated with the grain structure of the material, i.e. morphological anisotropy creating variations in grain boundary interactions; iv) microbands formation in D-direction is associated with local GND peaks; v) stress-relief crack propagating along grain boundaries due to the presence of voids or inclusions generates a 'shielding effect' on neighboring grains; and vi) the line average GND density profile within a single grain usually varies inversely with the width of the grain for A-, B- and D-directions, leading to generally pronounced higher GND density near triple junctions. Graphical abstract: The influence of grain morphology on shear band propensity in 7039-Al alloy with shear zone aligned in the A-, B-, C-, and D-directions is identified by EBSD maps and geometrically-necessary analysis. Rows: 1st, A; 2nd, B; 3rd, C; 4th, D. Columns: 1st, EBSD image plotted with MTEX with selected example region showing the GND density map (Scale bar: 100 μm); 2nd, total GND density map of the selected region (log10 scale, unit: 1/cm 2 ) with 20 μm scale bar; 3rd, GND density map of edge type dislocations (log10 scale, unit: 1/cm 2 ) with 20 μm scale bar; 4th, GND density map of screw type dislocations (log10 scale, unit: 1/cm 2 ) with 20 μm scale bar.